ANALYSIS OF EFFECTIVENESS AND EFFICIENCY IN BUDGET ABSORPTION - Sharaswati; Haliah; Nirwana (PT. Radja Intercontinental Publishing, 2024)
Population and Registration Service Civil Buton Regency is element organizer affairs government area in the field administration population and registration civil being​ authority area . Budget shopping at the Population and Registration Service Civil Buton Regency sourced from Budget Regional Income and Expenditures (APBD). Budget provided​ must used in a way Good . If given budget​ No walk in a way effective and efficient so give rise to impact form use budget misdirected spending , overspending​​​ mark budget (overspending ) , shop below mark budget (underspending) , and violating purchases provision law (fraud spending) . Study This aim For analyze realization budget shopping to effectiveness and efficiency absorption budget shopping at the Population and Registration Service Civil Buton Regency . Research methods used​ is method descriptive quantitative . Research result This show that level effectiveness absorption budget shopping For 2016 effective​ of 98.98%, effective in 2017 of 92.65%, effective in 2018 of 95.12%, effective in 2019 amounting to 96.94%, and effective in 2020 amounting to 91.46%. Efficiency level absorption budget shopping For 2016 is very efficient amounting to 41.36%, in 2017 it was very efficient amounting to 47.32%, in 2018 it was very efficient amounting to 51.36%, in 2019 it was efficient amounted to 64.82%, and 2020 was very efficient of 58.85%